Do We Really Need to Worry About Calcaneocuboid Subluxation During Lateral Column Lengthening for Planovalgus Foot Deformity?. Issue 4 (22nd October 2020) - Hedrick, Brittany; Riccio, Anthony; Siebert, Matthew; Shivers, Claire; Harris, Mitchell; Pierce, William A.; Thomas, Danielle M.; Zide, Jacob R.
Category: Midfoot/Forefoot; Other Introduction/Purpose: While lengthening of the lateral column through a calcaneal neck osteotomy is an integral component of flatfoot reconstruction in younger patients with flexible planovalgus deformities, the procedure has been implicated in iatrogenic calcaneocuboid (CC) subluxation and subsequent degenerative changes at the CC articulation. The purpose of this study is to characterize alterations at the CC joint following lateral column lengthening (LCL) as well as to determine if Steinman pin stabilization of the CC joint prior to distraction maintains a normal CC relationship. Methods: Seven matched pairs of fresh frozen cadaveric feet underwent pre-procedure plain radiography and cross-sectional computed tomography (CT) imaging. LCL via a calcaneal neck osteotomy was then performed. One foot of each matched pair had a single smooth Steinman pin placed centrally across the CC joint prior to osteotomy distraction. Distraction across each osteotomy was then performed and maintained with a 12mm porous titanium wedge. Repeat imaging was obtained and compared to pre-procedure studies to quantify sagittal and rotational differences at the CC articulation Results: Following LCL, plain radiography demonstrated statistically significant increases in the percentage of the calcaneal articular surface dorsal to the superior aspect of the cuboid in both the pinned (8.2% vs 17.6%, p=0.02) and unpinned (12.5% vs 16.3%, p=0.04) specimens. No difference in the percentage of subluxation was found between the two groups following LCL. CT imaging demonstrated statistically significant increases in rotation between the calcaneus and cuboid following LCL in both the pinned (7.6O +- 5.6O, p=0.01) and unpinned (17O +- 12.3O, p=0.01) specimens. Though a greater degree of rotation was present in the unpinned specimens following LCL, this difference was not statistically significant (p=0.28). Conclusion: Both sagittal and rotatory subluxation seem to occur at the CC joint following LCL regardless of pin stabilization. As a single pin would be expected to limit pure translation while having little effect on rotation, it is possible that the rotational changes identified on three-dimensional imaging are interpreted as dorsal translation when viewed two dimensionally using plain radiography. Consideration should therefore be given to CC stabilization with two pins during LCL to prevent this rotatory subluxation.